DOI: 10.31274/rtd-180813-13913
|View full text |Cite
|
Sign up to set email alerts
|

Selection for soybean seed yield with molecular markers

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly firom the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The coefficient was 0.30 for AX11056, 0.43 for AX11063, 0.38 for AX11080, and 0.53 for AX11104. Byrum (1999) reported nonsignificant ( P > 0.05) phenotypic correlation coefficients of 0.10, 0.25, and 0.37 between PRYT and replicated plots for three populations. Hegstad et al (1999) reported coefficients ranging from −0.04 to 0.41 with a mean of 0.17 between PRYT and replicated tests for five populations.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The coefficient was 0.30 for AX11056, 0.43 for AX11063, 0.38 for AX11080, and 0.53 for AX11104. Byrum (1999) reported nonsignificant ( P > 0.05) phenotypic correlation coefficients of 0.10, 0.25, and 0.37 between PRYT and replicated plots for three populations. Hegstad et al (1999) reported coefficients ranging from −0.04 to 0.41 with a mean of 0.17 between PRYT and replicated tests for five populations.…”
Section: Resultsmentioning
confidence: 91%
“…A breeder would like to advance the least percentage of lines from the initial evaluation to subsequent yield tests in multiple environments. The percentage of lines that had to be selected in the PRYT to retain the highest yielding line in the replicated tests ranged from 2 to 35% for the four populations, with an average of 14% (Table 4) Byrum (1999) reported that the selection intensities required in the PRYT to retain the highest yielding line in three populations were 16, 38, and 61%. In our study, an average selection intensity of only 3% was required in the PRYT to retain one of the 10 highest yielding lines in the replicated tests, but a mean selection intensity of 61% was required to retain all of the top 10 lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hegstad et al (1999) concluded that PRYT are effective for identification of elite soybean lines with high yield potential. Byrum (1999) proposed the use of molecular markers to increase the effectiveness of identifying high-yielding lines from PRYT. He concluded that the use of molecular markers alone or in combination with PRYT would be useful for selecting among lines for seed yield in a cultivar development program.…”
Section: Breeding and Testing Methodsmentioning
confidence: 99%